Exploring Work Motivation and Organizational Commitment on Work Effectiveness among Local Government Employees - Okurame, David E; Sirajudeen A. Fasasi; Emmanuel E Uye (MultiTech Publisher, 2024)
This study examined work motivation and organizational commitment on work effectiveness among local government employees in Oyo State, Nigeria. The study adopted cross-sectional survey design while simple random sampling method was used to select eight local government areas across four zones in Oyo State. Data were collected using validated scales from 180 employees. Data were analyzed using t-test of independent samples and multiple regression analysis. The result showed that work motivation and organizational commitment jointly and independently predicted work effectiveness among local government employee study participants. Also, age and work status significantly influenced work effectiveness. Concluding that work motivation and organizational commitment are strong predictors of work effectiveness. The study recommends introduction of management by objective to reward outstanding performance.